(3JegjO GdbhGYO TQM JSgjd GdahGFOs - (3eMH GdOjf eMeO Hf jhSa Hf CMeO GdMdHj GdeUQj GdeYQha H`` fGXQ GdLjTs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3GdeOQSI GdefUhQjI HGdbGgQI s)
(3ChdgG (B:s
(3hHYO, aEf cJGH JSgjd GdahGFO hJcejd GdebGUO GHf eGdc LGeY eajO aj eNJUQ SYjO s
(3BNQgG (B:s
(3eYfi GdLRGA de jLR GdYWa Ydjg bHdgG YfO Gdchajjf, hELGRI GHf GdSQGL hGdMeO ddg jJdhg Chd GdLRA GdKGfj s
(3HgG fXGe GdJYbjHIs
(3HgG CKQ WeSs
(3hGdNW eged GdfbW CMjGfkGs
(3aj GdeYgO fSNI CNQi GfXQgG aj GdLRA GdChd Qbe (B64 (3fMh s
(3fSNI KGfjI s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs